2020
DOI: 10.15460/eder.4.2.1427
|View full text |Cite
|
Sign up to set email alerts
|

Using design-based research to explore the influence of context in promoting pedagogical reform

Abstract: Many developing countries are seeking to improve the quality of education by promoting the use of learner-centred pedagogy as part of system wide reform.  Yet many studies reveal a gap between what is envisaged in policy and what happens in practice and the inherent limitations of uncritical adoption of 'best practice' from elsewhere into local contexts. Therefore design-based research (DBR), as an interventionist approach, was selected to investigate the conditions under which the innovation of learner-centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…However, instead of justifying individual methods or adapting them to the project's aims, many authors give an overview of their methodological choices in general, and often not very detailed: Some studies use a table or figure format to present and partially justify the empirical methods used in the reported projects (Delius, 2022;Di Biase, 2020;Lehtonen, 2021;Studer, 2021). In doing so, the authors embed the respective use of methods in the overall DBR projects.…”
Section: Orientation Towards Methodological Standards or Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, instead of justifying individual methods or adapting them to the project's aims, many authors give an overview of their methodological choices in general, and often not very detailed: Some studies use a table or figure format to present and partially justify the empirical methods used in the reported projects (Delius, 2022;Di Biase, 2020;Lehtonen, 2021;Studer, 2021). In doing so, the authors embed the respective use of methods in the overall DBR projects.…”
Section: Orientation Towards Methodological Standards or Requirementsmentioning
confidence: 99%
“…18, 29-30). Di Biase (2020) dedicates a chapter of her article to "A rationale for Design-based Research", outlining how the essential characteristics of DBR which "feature the interplay of theory and practice (…) were embedded in the research design" (Di Biase, 2020, p. 10). There are more articles using single DBR projects to illustrate methodological considerations (Euler & Collenberg, 2018;Gerholz et al, 2020;Gössling & Daniel, 2018).…”
Section: 31mentioning
confidence: 99%
“…Using an established DBR format (Di Biase, 2020), our research can be summarised in seven phases (Figure 1). Framework and criterion measure evaluated through factor analysis; exploratory, construct and criterion validity analyses carried out for the SJT simulation, emotion recognition exercise and attributional style measure Applied the framework to assess the capability of leaders working in particularly challenging international contexts where they and their teams face high levels of pressure III (a) Feedback and peer workshop with initial evaluation (Participant Group 2)…”
Section: Research Outlinementioning
confidence: 99%
“…Using an established DBR format (Di Biase, 2020), our research can be summarised in seven phases (Figure 1).…”
Section: The Applied Research Study – Research Questions and Overviewmentioning
confidence: 99%
“…Despite manifold possible contributions of EDR, our systematic review (Lehtonen et al, 2019) and the work of others (Anderson & Shattuck, 2012;McKenny & Reeves, 2019;Zheng, 2015) have indicated that most EDR researchers tend to focus on reporting their research contributions to educational practice and domain theories. A few researchers have reported how their EDR contributes to knowledge of design frameworks (e.g., Bergdahl et al, 2018;Lambert & Jacobsen, 2019) and design methodologies (e.g., Cowling & Birt, 2018;Di Biase, 2020). Therefore, there is a need for the dissemination of research that pays more attention to design frameworks and design methodologies so that those outside a particular EDR project can benefit.…”
Section: Introductionmentioning
confidence: 99%